2019
DOI: 10.1016/j.molp.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the Specificity of Protein Import into Chloroplasts and Mitochondria in Plant Cells

Abstract: Plants possess both types of endosymbiotic organelles, chloroplasts and mitochondria. Transit peptides and presequences function as signal sequences for specific import into chloroplasts and mitochondria, respectively. However, how these highly similar signal sequences confer the protein import specificity remains elusive. Here, we show that mitochondrial-or chloroplast-specific import involves two distinct steps, specificity determination and translocation across envelopes, which are mediated by the N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(97 citation statements)
references
References 59 publications
(126 reference statements)
8
89
0
Order By: Relevance
“…Thus, plant cells should have distinct mechanisms for protein targeting to the chloroplast and mitochondria (Schleiff and Becker, 2011;Garg and Gould, 2016). Indeed, we recently found that chloroplast transit peptides and presequences consist of two functionally different domains in plant cells (Lee et al, 2019). The N-terminal specificity domain confers import specificity, whereas the C-terminal domain is interchangeable between the transit peptide and presequence, and functions in the translocation of organellar proteins across the envelope membranes (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, plant cells should have distinct mechanisms for protein targeting to the chloroplast and mitochondria (Schleiff and Becker, 2011;Garg and Gould, 2016). Indeed, we recently found that chloroplast transit peptides and presequences consist of two functionally different domains in plant cells (Lee et al, 2019). The N-terminal specificity domain confers import specificity, whereas the C-terminal domain is interchangeable between the transit peptide and presequence, and functions in the translocation of organellar proteins across the envelope membranes (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we recently found that chloroplast transit peptides and presequences consist of two functionally different domains in plant cells (Lee et al, 2019). The N-terminal specificity domain confers import specificity, whereas the C-terminal domain is interchangeable between the transit peptide and presequence, and functions in the translocation of organellar proteins across the envelope membranes (Lee et al, 2019). The N-terminal specificity domain of the mitochondrial presequence contains two sequence elements: multiple arginine residues and a hydrophobic sequence motif (Abe et al, 2000;Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most N-terminal domain carries the charged residues critical for distinguishing between mitochondrial- and plastid targeting (Fig. 1), while the C-terminus is exchangeable 84 . Because the plastid is younger and because the photosynthetic organelle evolved in a eukaryotic cell instead of contributing to its actual origin, we understand more about the origin of the plastid NTS.…”
Section: Discussionmentioning
confidence: 99%